A study of the relationship between perceived leadership style of administrator and organizational commitment in public agencies / Afidah Sulong and Siti Khairuniza Ibrahim - Sulong, Afidah; Ibrahim, Siti Khairuniza (2006)
ASLI and INTAN are the agencies that have brought the concepts of the leadership in the public sector. These agencies were introduced to lead the improvement of the role of leadership that practiced by the administrators in the public agencies. The study examines the relationship between leadership styles of administrators and organisational commitment in public agencies. A sample size for the purpose of this study is 150, which indicate 50 respondents for each public agency that have been chosen. And the types of approach that used are by distributing questionnaire survey. From this study, there are four objectives that have been examined that are to determine the dominant style of leadership adopted by the administrators in the public agencies, to determine the level of organizational commitment in the public agencies, to explore the relationship between leadership styles with the organizational commitment and the to analyze the relationship between leadership style and three level of government. The study does not provide the strong relationship between the leadership and the organizational commitment in the public agencies. And each of level of government practiced a different leadership styles.